2013
DOI: 10.1371/journal.pone.0068257
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Ion Inhibits Nuclear Factor-Kappa B Activity in Human Oral Squamous Cell Carcinoma

Abstract: BackgroundThe spontaneous IL-8 secretion observed in OSCC is partially dependent on the disregulated activity of transcription factor NF-κB. Nickel compounds are well established human carcinogens, however, little is known about the influence of nickel on the spontaneous secretion of IL-8 in oral squamous cell carcinoma (OSCC) cells. The aim of the present study was to investigate whether Ni2+ ions can influence on IL-8 secretion by OSCC.Methods and ResultsThe IL-8 secretion was measured by ELISA. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The human OSCC cell line HSC3 (obtained from the Japanese Collection of Research Bioresources [JCRB] Cell Bank, Ibaraki, Japan) was maintained as described previously (14).…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human OSCC cell line HSC3 (obtained from the Japanese Collection of Research Bioresources [JCRB] Cell Bank, Ibaraki, Japan) was maintained as described previously (14).…”
Section: Cellsmentioning
confidence: 99%
“…The luciferase reporter vector encompassing the IL-8 untranslated region (UTR) was described previously (14). This vector contains two NF-κB-binding sites, and the shorter fragment, which contains only the lower binding site, was amplified and subcloned to the pGL4 basic vector (NF-κB-short vector) to eliminate the upper binding site.…”
Section: Deoxyribonucleic Acid (Dna) Constructionmentioning
confidence: 99%
“…NF-κB protein levels increase gradually from premalignant lesions to invasive cancer, indicating its role during the early stages of carcinogenesis [ 4 7 ]. In a previous study, we reported the inhibitory effect of Ni 2+ ions on NF-κB activity wherein, the ions directly bind to NF-κB p50 subunit and inhibit its nuclear transport, thereby, inhibiting IL-8 secretion [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we investigated the presence of inhibitory sites in order to ascertain the effect of a magnetic field on signal transduction pathways. Shionome et al reported that OSCC constantly activates the transcription factor NF-κB (28). Although PDGF-AA does not have a NF-κB binding site in the regulatory region, the action of PDGF-AA was observed by suppression of NF-κB using TPCK, a specific NF-κB-inhibitor.…”
Section: Discussionmentioning
confidence: 99%